2016 Rio Olympic Games: Can the schedule of events compromise athletes' performance?. (20th April 2016) - Rosa, João Paulo P.; Rodrigues, Dayane F.; Silva, Andressa; Moura Simim, Mário Antônio de; Costa, Varley T.; Noce, Franco; de Mello, Marco Túlio
ABSTRACT: The organizing committee of the 2016 Rio Olympic Games recently announced that some of the preliminary and final competitions will be held at night. The present article discusses the potential harmful effects of these late-night competitions on sleep, circadian rhythms and athletic performance during the Olympic Games. Specifically, night-time competition could lead to injury and may compromise an athlete's decision-making, attentional, physiological and other processes. Consequently, these impacts could negatively affect the performance of athletes and their teams. Thus, it is suggested that technical commissions take special care when creating strategies to minimize harm to the athletes by considering factors such as light exposure, melatonin intake, sleep hygiene and scheduled naps, and training at local competition time. Furthermore, it is necessary for specialists in chronobiology and sleep to engage with members of the national teams to develop an activity schedule for physical, technical, tactical and psychological preparation that accounts for circadian rhythms, thereby creating the best possible environment for the athletes to achieve their ideal performance.